IMPLEMENTASI APLIKASI GARUT INTAN UNTUK MENINGKATKAN PELAYANAN PUBLIK - Tina tresnasari (Advances in Police Science Research Journal, 2020)
ABSTRACT This research intend to determine how to analyze the benefit of the Online Garut Intan application in improving the public service. This research focused in some specific problems. The first one is the general description of the Online Garut Intan application, the second one is the implementation of the application itself to improve the public service, the third one is the factors that influenced the performance of the application itself. This research used qualitative approach with descriptive method with the data source such as: 1) Chief of Garut Resort Police 2) Head of traffic division of Garut Resort Police 3) the developer of online garut intan application 4) the operator of the application 5) local residents in the jurisdiction of garut resort police. The analysist methods used in this research are data reduction and conclusion focused methods. The research shows that 1) the application was used to ease the residents to find information about traffic activity in the jurisdiction of garut resort police. The locals that used the application has downloaded the apps from Google Playstore and registered themselves by filling their personal identity and phone number could get easy access on the features. 2) the performance are still in flaws despite it was used to increase public service effectivity. The lack of human resources are the main reason. 3) the factors that influenced the application in terms of increasing public service are grouped into 2 groups, the supporting factors and the obstacle factors. The first one is the supporting factors that include the support from the superiors to facilitate the apps itself to improve public service. The obstacle factors includes the lack of resources, handicapped internet and the lack on information to the locals. Advices for the superiors in implementing the online garut intan application is to improve the campaign on the apps itself by the traffic unit and spreading information all across the jurisdiction of garut resort police. Specific training skills especially in technology and information sectors are mandatory for all members of traffic unit. The traffic unit also need to determine the standard operation procdure and budgeting so the application could run professionally Keyword : Application; Garut Intan; Implementation; Online; Public Service